Tourism Industrial Linkages In Rwanda’s Economy - Pius ODUNGA (Journal of Tourism Economics and Policy, 2022)
Measurement of tourism economic impacts is important in monitoring progress towards meeting planned socio-economic goals. However, there has been insufficient attention to rigorous analysis of the ramifications of tourism beyond accounting for initial impacts. This study evaluates economic impacts of tourism in Rwanda by examining its effects on employment, labor incomes, and output and value addition. Rwanda’s 2014 Input-Output tables was used to compute direct, indirect, induced and total (SAM Type) multipliers which were interacted with internal tourism demand data from Rwanda’s 2014 tourism satellite account to estimate impacts. Labor income, output and value added multipliers indicate that tourism has strong linkages with service sectors, while the employment multiplier indicates robust linkages with agriculture. Results indicate that internal tourism demand created 29% of all jobs, generated 9.7% of labor incomes, 11.1% of total value addition and 12% of national output in 2014. Therefore, increasing internal tourism demand in Rwanda will lead to higher labor income, increased output and value addition and higher employment in agriculture and other associated sectors. This study’s main contribution is taking into account the predominantly informal sector of Rwanda’s economy especially with respect to the domestic tourism market. Future studies could estimate the magnitude of leakages from the economy through consumption and production processes.